S28 Changing diagnostic pattern of hiv and tuberculosis co-infection in england, wales and northern ireland, 2000–2014. (15th November 2017) - Winter, JR; Brown, J; Stagg, HR; Lalor, MK; Delpech, V; Lipman, M; Abubakar, I
Abstract : Background: HIV co-infection of tuberculosis (TB) patients is associated with TB disease progression, treatment complications, and higher mortality. Over the last decade, national guidelines have encouraged earlier diagnosis of HIV infection and greater use of anti-retroviral therapy (ART). We investigated the relationship between HIV and TB diagnoses at a national level. Methods: TB patients aged ≥15 years notified to Public Health England from 2000–2014 were linked to national HIV surveillance data. Amongst co-infected patients, we examined the order of TB and HIV diagnoses. Diagnoses were classed as 'simultaneous' if TB and HIV were diagnosed within 91 days of each other. Results: 106, 829 TB cases aged ≥15 years were notified to PHE between 2000 and 2014, of which 5792 (5.4%) were co-infected with HIV. The absolute number of HIV-TB diagnoses rose between 2000–2004, and then decreased from 543 (8.0%) in 2004 to 205 (3.2%) in 2014. Overall, 2, 787/5, 792 (49%) were diagnosed with TB and HIV simultaneously, whilst 549 (9%) were diagnosed with TB before and 2456 (42%) after HIV diagnosis. The relationship between TB and HIV diagnosis changed over time (figure 1 ). The absolute number of TB cases in people with known HIV rose from 75/224 (33%) in 2000 to 210/454 (46%) in 2007, then fell to 117/205 (57%) by 2014, but increased as a proportion of all HIV-TB cases from 2000 to 2014. There were corresponding declines in the proportion diagnosed simultaneously with TB and HIV from 298/543 (55%) in 2004 to 79/205 (39%) in 2014 and those first diagnosed with TB (51/224 (23%) in 2000 to 9/205 (4%) in 2014). Conclusions: Within an overall decline in HIV-TB co-infection there has been a change in the pattern of co-infection. A greater proportion of cases now occur in people with known HIV infection, and fewer HIV infections are diagnosed after TB diagnosis. This may be explained by more HIV testing, including in TB clinics, resulting in earlier HIV diagnosis. However, as the number of people with HIV in the UK increases, sustained success requires better management of latent TB infection to prevent the occurrence of TB disease in people diagnosed with HIV.